Developing social marketed individual preconception care consultations: Which consumer preferences should it meet?. (25th April 2017) - van Voorst, Sabine F.; ten Kate, Chantal A.; de Jong‐Potjer, Lieke C.; Steegers, Eric A. P.; Denktaş, Semiha
Abstract: Aims: Preconception care (PCC) is care that aims to improve the health of offspring by addressing risk factors in the pre‐pregnancy period. Consultations are recognized as a method to promote perinatal health. However, prospective parents underutilize PCC services. Uptake can improve if delivery approaches satisfy consumer preferences. Aim of this study was to identify preferences of women (consumers) as a first step to social marketed individual PCC consultations. Methods: In depth, semi‐structured interviews were performed to identify women's views regarding the four components of the social marketing model: product (individual PCC consultation), place (setting), promotion (how women are made aware of the product) and price (costs). Participants were recruited from general practices and a midwife's practice. Content analysis was performed by systematic coding with NVIVO software. Results: The 39 participants reflected a multiethnic intermediately educated population. Product: Many participants had little knowledge of the need and the benefits of the product. Regarding the content of PCC, they wish to address fertility concerns and social aspects of parenthood. PCC was seen as an informing and coaching service with a predominant role for health‐care professionals. Place: the general practitioner and midwife setting was the most mentioned setting. Promotion: A professional led promotion approach was preferred. Price: Introduction of a fee for PCC consultations will make people reconsider their need for a consultation and could exclude vulnerable patients from utilization. Conclusion: This study provides consumer orientated data to design a social marketed delivery approach for individual PCC consultations.